Biblioterapia w edukacji inkluzyjnej - Chatzipentidis, Kiriakos (2017)
Introduction: Given work presents and describes possible uses of reading therapy – bibliotherapy in the field of inclusive education. The author outlines the definitions of bibliotherapy, its advantages and functions, describes the structure of the bibliotherapeutic session within the inclusive class, gives criteria for the selection of inclusion bibliotherapy literature, and then discusses the role of bibliotherapy in the professional development of teachers. Method: In given work author has reviewed the articles published in foreign scientific journals exploring use of bibliotherapy in the field of inclusion pedagogy. Results: Bibliotherapy enables empathy, understanding and acceptance, teaches positive coping strategies in difficult life situations, and strengthens co-operation between children. In addition, it provides an opportunity for the professional development of teachers. Conclusions: In conclusion, the author points out the great potential of bibliotherapy in the movement for inclusive education.
Keywords: reading therapy; professional development of teachers; bibliotherapy; inclusive education; inclusive pedagogy